Rancang Bangun Alat Pemotong Kentang Stick Dengan Menggunakan Mesin Penggerak Dinamo Listrik Skala Rumah Tangga - Aji, Deva Dian Satrio; Murdianto, Deny; Nurdin, Muhammad Firdan (Journal BEARINGS: Borneo Mechanical Engineering and Science, 2024)
The processing of potato into fried potato sticks is one of the popular fastfood processing in Indonesia. One of the entrepreneurs in Tarakan City named Randi still uses manual tools to cut potatoes into the fried potato sticks, so the process is less efficient and effective. To solving this problem, it is necessary to create a potato stick cutting machine that is economically valuable. The purpose of this research is to design an potato stick machine. Based on the final design, the electric motor used is a single-phase AC gearbox motor with a power of 0.18 kW at 41.7 rpm, which is transmitted using a type B V-belt to the potato cutter. The test results of this potato stick cutting machine show a potato stick cutting capacity of 192.17 kg/hour with an electricity usage cost of Rp. 187.84/hour.